Generalisierte erythrosquamöse Dermatose - Weberschock, Tanja; Haußer-Siller, Ingrid; Gholam, Patrick; Hartmann, Martin (Der Hautarzt, 2012)
A 21-year-old man presented with generalized erythema, erosions and hyperkeratoses since birth. Histology revealed epidermolytic hyperkeratosis with degeneration of the upper epidermis and perinuclear deposits of abnormal keratin aggregations. Epidermolytic ichthyosis was diagnosed. This congenital Ichthyosis occurs due to mutations of keratin 1 or 10 genes that leads to defects of intra- and intercellular structural integrity in the spinous and granular layers with compensatory hyperkeratosis. After childhood, life expectancy is normal but lifelong therapeutic and skin care measures are required.